The journalist of Castro Street : the life of Randy Shilts - Stoner, Andrew E. (University of Illinois Press, 2019)
"Randy Shilts is often named as the first openly gay reporter to earn a full-time reporting position for a major daily newspaper. He is regularly included in the ranks of America's most important journalists-turned-author, and his books, And the Band Played On and The Mayor of Castro Street, had a clear impact on America. Andrew Stoner reveals that, while Shilts's arrival at The San Francisco Chronicle did not make him the first gay reporter at a major daily, he did have a prolific and distinctive writing career matched by few. Shilts's focus on issues related to the role of gay, lesbian, bisexual and transgendered people in society paved the way for a relentless drive to focus political, clinical and societal attention on the rising tide of HIV and AIDS. Reporter functions revealed by Shilts reveal a commitment to exerting a strong journalistic influence over society and media consumers to help further understanding and advancement of homosexual liberation while personal and professional interviews reveal Shilts's work as both a reporter and noted author were heavily influenced by his open attitudes about disclosure of his sexual orientation from the start of his career and his desire to explain or unpack aspects of gay culture, and ultimately the AIDS crisis, to heterosexual audiences. His personal transparency related to his sexuality, however, stood in marked contrast to his carefully constructed closet to conceal his own HIV infection. Stoner carefully examines the posthumous critique of Shilts's work, including a malevolent relationship existing between Shilts and other gay journalists, authors and leaders, particularly around his presentation of the so-called "Patient Zero" to explain the AIDS pandemic"--